Neonatal outcomes in elective repeated caesarean section at term pregnancy - Vian Rbhass Sherwani; Ishraq Mahmood Shakir (Diyala Journal of Medicine, 2018)
Background: Caesarean delivery is associated with adverse health outcomes on both women and newborn infant. Timing of elective caesarean delivery also had an effect on the neonatal outcomes.